Waists, health and history: obesity in nineteenth century Britain - Campbell, S (2014)
The scale of the current global obesity epidemic and the implications of this for health, functionality and economics, dictates that assessing the origins of overnutrition must become a priority in all research fields. To date anthropometric historians have mainly utilised institutional sources providing height and occasionally weight data for a sample of the working class who experienced deprivation. Tailoring institutions offer new, innovative sources for the field; uniquely measuring body shape in its entirety and sampling the upper-middle classes and elites. Anthropometric data for waist circumference, hip circumference and leg length has been collected from Morris & Son tailoring establishment in Barmouth, North West Wales and from Henry Poole & Co. ‘Savile Row’ tailors in Mayfair, London. This data from the second half of the nineteenth century has been nominally linked to census and probate records and cross-referenced with contemporary medical tracts and modern epidemiological literature to highlight obesity related health risks within both populations. Results indicate that 'diseases of affluence' permeated many nineteenth century class groups. Both waist circumferences and hip circumferences increased over the life span. Furthermore, Barmouth’s economic transition from a port to a tourist destination appears to have placed individuals' health (when measured by early adult waist-hip ratio) at greater risk than the overall wealthier customers attending Savile Row. The Barker hypothesis may be relevant - an influx of wealth being of greater detriment to health in later life than consistent affluence. For Henry Poole & Co.’s customers an elite lifestyle enabled girths to expand, increasing the risk of chronic diseases but seemingly protecting them from infectious pathogens. In later life, during the second half of the nineteenth century, it would appear that optimal waist circumferences to reduce mortality were larger than current recommended levels.